Neuroimmunophysiology of the gut: advances and emerging concepts focusing on the epithelium. Issue 12 (December 2018) - Sharkey, Keith; Beck, Paul; McKay, Derek
Abstract The epithelial lining of the gastrointestinal tract serves as the interface for digestion and absorption of nutrients and water and as a defensive barrier. The defensive functions of the intestinal epithelium are remarkable considering that the gut lumen is home to trillions of resident bacteria, fungi and protozoa (collectively, the intestinal microbiota) that must be prevented from translocation across the epithelial barrier. Imbalances in the relationship between the intestinal microbiota and the host lead to the manifestation of diseases that range from disorders of motility and sensation (IBS) and intestinal inflammation (IBD) to behavioural and metabolic disorders, including autism and obesity. The latest discoveries shed light on the sophisticated intracellular, intercellular and interkingdom signalling mechanisms of host defence that involve epithelial and enteroendocrine cells, the enteric nervous system and the immune system. Together, they maintain homeostasis by integrating luminal signals, including those derived from the microbiota, to regulate the physiology of the gastrointestinal tract in health and disease. Therapeutic strategies are being developed that target these signalling systems to improve the resilience of the gut and treat the symptoms of gastrointestinal disease. In this Review, the authors summarize how various interactions at the gastrointestinal epithelium regulate gut physiology. They also discuss how neuroimmunophysiology has advanced the understanding of gastrointestinal pathophysiology with the potential to reveal novel therapies for disorders such as IBS and IBD. Key points The gastrointestinal epithelium allows the absorption of nutrients, water and immune surveillance while simultaneously limiting the translocation of potentially harmful antigens and commensal and pathogenic microorganisms. Disturbances in the barrier function of the gastrointestinal tract lead to the development or exacerbation of disease that can manifest locally in the gut wall or involve distant organs including the brain. Intestinal barrier function is regulated by multidirectional interactions between epithelial (enteroendocrine, tuft, goblet and Paneth) cells and the enteric nervous and immune systems. The intestinal microbiota is a key element in sophisticated intracellular, intercellular and interkingdom signalling systems that regulate intestinal barrier function. Therapeutic strategies are being developed that target these signalling systems to increase the resilience of the gastrointestinal tract and limit disturbances in barrier function.